The siren, the song, and the spy - Tokuda-Hall, Maggie (Tokuda-Hall, Maggie. Mermaid, the witch, and the sea (Series), 2023)
"By sinking a fleet of Imperial Warships, the Pirate Supreme and their resistance fighters have struck a massive blow against the Emperor. Now allies from across the empire are readying themselves, hoping against hope to bring about the end of the conquerors' rule and the rebirth of the Sea. But trust and truth are hard to come by in this complex world of mermaids, spies, warriors, and aristocrats. Who will Genevieve--lavishly dressed but washed up, half-dead, on the Wariuta island shore--turn out to be? Is warrior Koa's kindness toward her admirable, or is his sister Kaia's sharp suspicion wiser? And back in the capital, will pirate-spy Alfie really betray the Imperials who have shown him affection, especially when a duplicitous senator reveals he would like nothing better? Meanwhile, the Sea is losing more and more of herself as her daughters continue to be brutally hunted, and the Empire continues to expand through profits made from their blood. The threads of time, a web of schemes, shifting loyalties, and blossoming identities converge in Maggie Tokuda-Hall's remarkable companion to The Mermaid, the Witch, and the Sea, as unlikely young allies work to forge a new and better world"--